Analysis of the Parent Company and a Subsidiary Company Concept in Article 5 of the Law on Companies of the Republic of Lithuania - Bakanauskas, Edvinas (Teisė, 2020)
The present article analyses the concept of a parent and a subsidiary company as defined in Article 5 of the Law on Companies of the Republic of Lithuania. The article also examines the relationship between companies, the concept of control, evaluates concept of parent company and subsidiary in the context of European Model Company Act (EMCA).